A confounding case of pancytopenia - C., Vignesh; K., Mahendra kumar (International Journal of Advances in Medicine, 2022)
Tuberculosis is one of the major health problems in the developing countries like India. Due to its nonspecific presentation, extra pulmonary TB is diagnosed at later stages.It is an important differential diagnosis for pyrexia of unknown origin (PUO). A 54-year-old male came to hospital with complaints of fever, pain abdomen (on and off), easy fatiguability, reduced appetite, weight loss, breathlessness on exertion for 8 months who completely recovered after starting anti-tubercular therapy.